The effect of cooperative learning model of team game tournament (TGT) type on students mathematical learning achievement of junior high school - Muhammad Arifuddin; Laila Hayati; Amrullah Amrullah; Baidowi Baidowi (Jurnal Pijar Mipa, 2021)
This research aims to find out the effect of cooperative learning models of the Teams Games Tournament (TGT) type on the studentsÃ¢â¬â¢ mathematics learning achievement of the 8th-grade students of SMPN 13 Mataram Academic Year 2019/2020. This study is a quasi-experimental with the post-test only non-equivalent control group design type. The population of the research was the whole 8th-grade students of SMPN 13 Mataram Academic Year 2019/2020. In determining the sample, probability sampling was being used in the of form cluster random sampling, the sample of the research was the VIII-A class as the experimental class and VIII-B class as the controlling class. The instrumen which was used in this research was the test of the students learning achievement (post-test). Quantitave analysis obtained by using t-test. The results of this research showed that there were differences in students learning outcomes with the TGT type cooperative model and direct learning model students. By the effect size method, we obtain that the effect of TGT type on the student's achievement was high category. Furthermore, thatÃ¢â¬â¢s mean that TGT type can be given a high effect on students' achievement in the concept of linear equation system for two variables. For teachers, especially in SMPN 13 Mataram should be an alternative learning model of the TGT cooperative model as an one of the next mathematics learning.